Challenge and Solution of Election Supervisory Agency in Enforcing E-Voting Law for Transparent and Efficient Election - Muhammad Daffa Al Khairi Lubis (Journal of Political Innovation and Analysis, 2026)
Background: General elections constitute a fundamental democratic mechanism through which citizens exercise their right to choose government representatives; however, voter participation in Indonesia remains relatively low, as evidenced by persistently high Golongan Putih (Golput) rates from 2004 to 2024. This condition reflects ongoing public distrust in the electoral system, driven by perceptions of fraud, limited transparency, and dissatisfaction with the performance of elected leaders, which in turn threatens democratic legitimacy and political stability. Objective: This study proposes the adoption of an electronic voting system utilizing smart cards and multi-touchscreen technology as a potential solution to address these challenges. Method: The proposal draws on successful implementations in countries such as India and Brazil, as well as pilot experiences in Jembrana, Bali. Findings and Implications: E-voting is expected to enhance electoral efficiency, transparency, and accuracy while reducing the risks of fraud and human error, provided that robust data security measures are implemented to safeguard system integrity against cyber threats. The implementation of a modern and reliable e-voting system is therefore expected to restore public confidence in the electoral process, expand secure and accessible voting opportunities, and increase voter participation. Conclusion: Ultimately, this would strengthen democratic governance by ensuring that election outcomes more accurately reflect the aspirations and will of the people.